2017
DOI: 10.17554/j.issn.2311-5106.2017.04.222
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the Changings of Blood Coagulation Fibrinolysis Markers Before and After Spinal Surgery in Adolescent and Elderly Patients

Abstract: adolescent idiopathic scoliosis (AIS) patients (3 boys, 24 girls; mean age 15 years) underwent instrumentation for posterior fusion. 29 lumbar spinal canal stenosis (LSCS) patients (15 men, 14 women; mean age 71 years) underwent laminectomy for posterior decompression. Plasma levels of soluble fibrin monomer complex (SFMC), D-dimer, and plasminogen activator inhibitor type 1 (PAI-1) were measured at 1 day preoperatively and on postoperative days (PODs) 1, 3, and 7. RESULTS: The SFMC level showed significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Literature has shown that FM can be used to detect hypercoagulable states during the surgical period, for example, increased FM on POD1 was associated with DVT development. 42,43 Similar to VTE, these studies have also shown using FM and DD together is more accurate for diagnosing early post-op DVTs. More research is needed comparing FM levels prior to, during and after surgery, as well as how DVT prophylaxis during the surgical period (whether anti-coagulants or compression stockings) could affect FM.…”
Section: Discussionmentioning
confidence: 86%
“…Literature has shown that FM can be used to detect hypercoagulable states during the surgical period, for example, increased FM on POD1 was associated with DVT development. 42,43 Similar to VTE, these studies have also shown using FM and DD together is more accurate for diagnosing early post-op DVTs. More research is needed comparing FM levels prior to, during and after surgery, as well as how DVT prophylaxis during the surgical period (whether anti-coagulants or compression stockings) could affect FM.…”
Section: Discussionmentioning
confidence: 86%